Biotin–Thiamine Responsive Basal Ganglia Disease: A Treatable Metabolic Encephalopathy—Not to Be Missed! - Nemani, Tarishi; Mehta, Puja; Udwadia-Hegde, Anaita (Journal of Pediatric Neurology, 2020)
Biotin–thiamine responsive basal ganglia disease (BTBGD) is an autosomal recessive neurometabolic disorder, characterized by encephalopathy, extrapyramidal signs following mild infection, trauma or surgery and is potentially reversible with treatment. We describe a 15-month-old female child of Indian-Muslim origin with characteristic clinical and radiological features of BTBGD that showed complete resolution with treatment. A comparison with previously reported cases reveals a different mutation (exon 2 vs. exon 5 in middle east cases) in the SLC19A3 gene that could be specific for the Indian subcontinent. We also emphasize the importance of a trial of vitamins in patients with acute metabolic encephalopathy.
Keywords: biotin–thiamine responsive basal ganglia disease; SLC19A3 gene; encephalopathy